(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Mahesh Dattani addresses the subject of Gender discrimination in his play Tara. This article attempts to discuss and analyze the issue of marginalizing women in the play. Chandan is the preferred son over Tara, a girl from an Indian family. This paper is an attempt to study sexism in a society, the injustice done based solely on gender and preference for boys over girls in an Indian family. The play also deals with the emotional and physical separation of conjoined twins. The play presents the patriarchal system that is deeply rooted in society. Women act as the key in the hands of the patriarchy to maintain patriarchal values. In this play, Bharati, despite being Tara’s mother, ruined her daughter’s life and suffered in the long run for her inhuman act. Through this work, Dattani exposed society’s insensitive treatment of people with disabilities. Dr. Thakkar abuses his profession as a science and technology person. He was bribed by Bharati and her father to perform an operation that resulted in Tara’s death.